Peran Kejaksaan Negeri Purbalingga Dalam Proses Penyelidikan Perkara Tindak Pidana Korupsi Pengelolaan Anggaran Pendapatan Dan Belanja Daerah - Wahyudi, Bellinda Nabilla Faradiva; Amarini, Indriati (UMPurwokerto Law Review, 2024)
Abstract The Prosecutor's Office is a form of law enforcement established by the state in accordance with its duties and authorities in the exercise of state power in the field of law, in this case it is one of the main pillars of the government in exercising state power in the field of prosecution, investigation, and investigation as well as other authorities based on the Law, carried out independently. The settlement of a corruption case is in line with the role of the Prosecutor's Office as an institution that has the authority to exercise state power. The problems in this study include how the role of the Purbalingga District Attorney's Office is in line with the series of flows taken in the investigation stage of corruption cases in the management of the regional revenue and expenditure budget (APBD) of Purbalingga District, Purbalingga Regency, as well as the obstacles faced by the investigating team in carrying out the investigation process for corruption in the management of the regional revenue and expenditure budget (APBD) of Purbalingga District. Purbalingga District. The research method used by the authors in this study is normative juridical, with secondary data sources. The data collection method used in this study is a library study (Library Research), as well as interviews with related parties to complete secondary data. From the research that has been carried out, the Purbalingga District Attorney's Office has done its role well in solving corruption cases in the management of the regional budget (APBD), although obstacles are still encountered during the investigation process. Keywords: the role of the prosecutor's office, investigation, corruption in the management of regional budgets and expenditures (APBD) Abstrak Kejaksaan merupakan salah satu wujud dari penegakan hukum yang dibentuk oleh negara sesuai dengan tugas serta kewenangannya dalam pelaksanaan kekuasaan negara di bidang hukum, dalam hal ini merupakan salah satu pilar utama pemerintah dalam melaksanakan kekuasaan negara dibidang penuntutan, penyidikan, dan penyelidikan serta kewenangan lain berdasarkan Undang-Undang, dilaksanakan secara merdeka. Penyelesaian suatu perkara tindak pidana korupsi sejalan dengan peran Kejaksaan sebagai lembaga yang memiliki kewenangan untuk melaksanakan kekuasaan negara. Permasalahan dalam penelitian ini mencakup bagaimana peran dari Kejaksaan Negeri Purbalingga sejalan dengan rangkaian alur yang ditempuh dalam tahap penyelidikan perkara tindak pidana korupsi pengelolaan anggaran pendapatan dan belanja daerah (APBD) Kecamatan Purbalingga Kabupaten Purbalingga, serta hambatan yang dihadapi oleh tim penyelidik dalam menjalankan proses penyelidikan perkara tindak pidana korupsi pengelolaan anggaran pendapatan dan belanja daerah (APBD) Kecamatan Purbalingga Kabupaten Purbalingga. Metode penelitian yang digunakan oleh penulis dalam penelitian ini adalah yuridis normatif, dengan sumber data sekunder. Metode pengumpulan data yang digunakan dalam penelitian ini adalah studi kepustakaan (Library Research), serta wawancara dengan pihak terkait guna melengkapi data sekunder. Dari penelitian yang sudah dilaksanakan, Kejaksaan Negeri Purbalingga sudah melakukan perannya dengan baik dalam penyelesaian perkara tindak pidana korupsi pengelolaan anggaran pendapatan dan belanja daerah (APBD), meskipun masih ditemui hambatan saat berjalannya proses penyelidikan. Kata kunci: peran kejaksaan, penyelidikan, korupsi dalam pengelolaan anggaran pedapatan dan belanja daerah (APBD)